Nutrient exchange and denitrification on reef balls in the Chesapeake Bay - Jeffrey C. Cornwell; Michael S. Owens; Melanie Jackson; Allison M. Colden (Ecological Engineering, 2026)

Opportunities and Challenges for Including Oyster-Mediated Denitrification in Nitrogen Management Plans - Julie M. Rose; J. Stephen Gosnell; Suzanne Bricker; Mark J. Brush; Allison Colden; Lora Harris; Eric Karplus; Alix Laferriere; Nathaniel H. Merrill; Tammy B. Murphy; Joshua Reitsma; Johnny Shockley; et al. (Estuaries and Coasts, 2021)
Nitrogen pollution is one of the primary threats to coastal water quality globally, and governmental regulations and marine policy are increasingly requiring nitrogen remediation in management programs. Traditional mitigation strategies (e.g., advanced wastewater treatment) are not always enough to meet reduction goals. Novel opportunities for additional nitrogen reduction are needed to develop a portfolio of long-term solutions. Increasingly, in situ nitrogen reduction practices are providing a complementary management approach to the traditional source control and treatment, including recognition of potential contributions of coastal bivalve shellfish. While policy interest in bivalves has focused primarily on nitrogen removal via biomass harvest, bivalves can also contribute to nitrogen removal by enhancing denitrification (the microbial driven process of bioavailable nitrogen transformation to di-nitrogen gas). Recent evidence suggests that nitrogen removed via enhanced denitrification may eclipse nitrogen removal through biomass harvest alone. With a few exceptions, bivalve-enhanced denitrification has yet to be incorporated into water quality policy. Here, we focus on oysters in considering how this issue may be addressed. We discuss policy options to support expansion of oyster-mediated denitrification, describe the practical considerations for incorporation into nitrogen management, and summarize the current state of the field in accounting for denitrification in oyster habitats. When considered against alternative nitrogen control strategies, we argue that enhanced denitrification associated with oysters should be included in a full suite of nitrogen removal strategies, but with the recognition that denitrification associated with oyster habitats will not alone solve our excess nitrogen loading problem.

Voluntary Restoration: Mitigation's Silent Partner in the Quest to Reverse Coastal Wetland Loss in the USA - Rachel K. Gittman; Christopher J. Baillie; Katie K. Arkema; Richard O. Bennett; Jeff Benoit; Seth Blitch; Julien Brun; Anthony Chatwin; Allison Colden; Alyssa Dausman; Bryan DeAngelis; Nathaniel Herold; et al. (Frontiers in Marine Science, 2019)

Sediment Suspension and Deposition Across Restored Oyster Reefs of Varying Orientation to Flow: Implications for Restoration - Allison M. Colden; Kelsey A. Fall; Grace M. Cartwright; Carl T. Friedrichs (Estuaries and Coasts, 2016)